Oxygen Sensitivity of Reporter Genes: Implications for Preclinical Imaging of Tumor Hypoxia - Ivana Cecic; Denise A. Chan; Patrick D. Sutphin; Pritha Ray; Sanjiv Sam Gambhir; Amato J. Giaccia; Edward E. Graves (Molecular Imaging)
Reporter gene techniques have been applied toward studying the physiologic phenomena associated with tumor hypoxia, a negative prognostic indicator. The purpose of this study was to assess the potential adverse effects of hypoxic conditions on the effectiveness of four commonly used reporter genes: Renilla luciferase, monomeric red fluorescent protein, thymidine kinase, and lacZ . Tumor-forming A375 cells expressing a trifusion reporter consisting of Renilla luciferase, monomeric red fluorescent protein, and thymidine kinase were subjected to decreasing oxygen tensions and assayed for reporter expression and activity. A375 cells expressing β-galactosidase were similarly exposed to hypoxia, with activity of the reporter monitored by cleavage of the fluorescent substrate 7-hydroxy-9 H -(1, 3-dichloro-9, 9-dimethylacridin-2-one)-β-galactoside (DDAOG). Generation of signal in in vivo tumor models expressing bioluminescent or β-galactosidase reporters were also examined over the course of hypoxic stresses, either by tumor clamping or the antivascular agent 5, 6-dimethylxanthenone-4-acetic acid (DMXAA). Our findings indicate that bioluminescent and fluorescent reporter activity are decreased under hypoxia despite minimal variations in protein production, whereas β-galactosidase reporter activity per unit protein was unchanged. These results demonstrate that combining β-galactosidase with the DDAOG optical probe may be a robust reporter system for the in vivo study of tumor hypoxia.